A Phenomenological Inquiry Into the Freelancers' Work Motivation, Needs and Challenges: An Emerging Economy Perspective - Shaleen, Mehrab; Haque, Mahbubul (International Journal of Qualitative Research, 2024)
Freelancing has been assumed as a possible remedy for unemployment by the Bangladeshi youth for some time now. This research is conducted to investigate the profession of a freelancer in Bangladesh and focuses on the motivational stages undergone by freelancers and their plans. Moreover, the study attempts to explain to what extent the needs of freelancers are satisfied from the standpoint of Maslow’s Hierarchy of Needs theory. For this purpose, a qualitative methodology i.e., phenomenology is used. Fifteen respondents working in different parts of the capital city took part in the interview for this study.  The study has demonstrated that an overwhelming majority of the respondents acknowledged it as an opportunity at first that gradually helps to develop an entrepreneurial mindset. One striking feature of the findings, however, is that freelancing may be a solution provisionally but not in the long run due to unfulfilled dimensions of the need theory. A few directions for future works are also suggested in this regard.